Nutrition Counseling to Strengthen Knowledge of Balanced Nutrition and Healthy Living Behaviors among Elementary School Students - Egil Agnas Miranda; Laras Rasi Alviola; Vania Putri Naifa; Muthiana Zakiya; Rifky Miftahurrahman; Faiza Chalisa Yufra; Fhadilla Amelia (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Nutrition counseling is an educational approach aimed at improving nutritional knowledge and encouraging the adoption of Clean and Healthy Living Behavior (PHBS) among school-aged children. This age group are in a period of rapid growth and development. However, many still face nutritional problems and unhealthy behavioral practices. This activity aimed to examine the effect of nutrition counseling on balanced nutrition knowledge, understanding of the Isi Piringku concept, and the implementation of PHBS among elementary school students. The activity was conducted at SDN 23 Marapalam, Padang City, involving 30 students. Nutrition counseling was delivered individually through interactive discussions supported by educational media, including posters and food photo books. Evaluation was carried out using pre-test and post-test instruments to assess changes in students’ knowledge, as well as monitoring of PHBS implementation. Data were analyzed descriptively and using the Wilcoxon Signed Rank Test. The results showed an increase in the mean knowledge score from 95.3 before counseling to 99.3 after counseling. However, the increase was not statistically significant (p>0.05). Most students had already demonstrated good nutritional knowledge at baseline. On the other hand, the majority of students had not consistently implemented PHBS, although several positive behavioral changes were observed. Therefore, nutrition counseling plays a role in strengthening students’ knowledge and initial awareness of nutrition and healthy living behaviors. However, continuous counseling and long-term mentoring are required to promote consistent behavioral change.